Memutus Rantai Hambatan Belajar: Analisis Kedalaman Berpikir Konseptual dalam Aljabar Elementer. - Purwasih, Silviana Maya; Faizah, Hanim; Prajitno, Sunyoto Hadi (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study characterizes learning obstacles in elementary algebra among pre-service mathematics teachers to address gaps in conceptual and reflective thinking that are frequently overshadowed by purely procedural mastery. Design/methodology/approach: Adopting a descriptive qualitative design, this research involved three mathematics education students at Universitas PGRI Adi Buana Surabaya. Data were gathered through problem-solving tests and in-depth interviews, subsequently analyzed using the Miles-Huberman model and validated through technical triangulation. Findings: The results identify three primary categories of obstacles: (1) ontogenic (anxiety and carelessness); (2) didactic (entrenched procedural learning habits); and (3) epistemological (conceptual misconceptions). These interconnected barriers significantly impede students' capacity to construct sound mathematical knowledge. Practical implications: It is recommended that educators implement error analysis and metacognitive reflection strategies to facilitate the reconstruction of robust conceptual frameworks among students. Originality/value: The significance of this research lies in its comprehensive mapping of psychological and cognitive obstacles occurring simultaneously, providing a strategic foundation for targeted pedagogical interventions in Elementary Algebra courses..   Purpose: Penelitian ini mendeskripsikan hambatan belajar aljabar elementer mahasiswa calon guru guna mengatasi kendala berpikir konseptual dan reflektif yang sering terabaikan oleh penguasaan prosedural semata. Design/methodology/approach: Studi deskriptif kualitatif ini melibatkan tiga mahasiswa Pendidikan Matematika Universitas PGRI Adi Buana Surabaya. Data dikumpulkan melalui tes pemecahan masalah dan wawancara, lalu dianalisis menggunakan model Miles-Huberman dengan validasi triangulasi teknik. Findings: Temuan mengungkap tiga hambatan utama: (1) ontogenik (kecemasan dan ketidaktelitian); (2) didaktik (kebiasaan belajar prosedural); dan (3) epistemologis (miskonsepsi konsep). Keterkaitan hambatan tersebut berdampak signifikan pada rendahnya kemampuan mahasiswa mengonstruksi pengetahuan matematis. Practical implications: Pendidik direkomendasikan menerapkan strategi analisis kesalahan (error analysis) dan refleksi metakognitif untuk membantu mahasiswa membangun kembali pemahaman konseptual yang kokoh. Originality/value: Keunggulan penelitian ini terletak pada pemetaan hambatan belajar yang menggabungkan aspek psikologis dan kognitif secara simultan sebagai landasan intervensi pedagogis tepat sasaran dalam mata kuliah Aljabar Elementer.